Legal Politics Village Government Policies in Organizing Village-Owned Enterprises Based on Creative Economy - Bayu Mogana Putra; Ridwan Adnan Erlangga (Research Synergy Foundation, 2022)
The development of the creative economy continues to experience high productivity. It must be well adopted by creative economic actors, not least by a government-owned enterprise with very potential, namely the Village Owned Enterprise. This scientific paper aims to analyze and reveal the legal politics of village government policies in implementing Village Owned Enterprises based on a creative economy to improve the local economy by utilizing regional potential. The method used was a normative legal research method, namely by examining the concept of law as a principle of justice in the moral system and as a rule in legislation under the research focus in this scientific paper. The analysis in this scientific paper used three research approaches, namely the philosophical approach, the legislative approach, and the conceptual approach. In the end, the analysis and research revealed the ideal political-legal policy direction to be implemented by the village government in the implementation of a creative economy-based Business Entity by utilizing local potential to be developed and managed to create a productive and innovative economic activity. Therefore, it could support the improvement of the community's economy.